PENERAPAN STRATEGI AKTIVITAS MENULIS TERBIMBING (SAMT) UNTUK MENINGAKATAN KETERAMPILAN MENULIS TEKS PENGUMUMAN SISWA KELAS VII SMP NEGERI 7 RAMBAH ROKAN HULU - Pon Gunawan (JURNAL PAJAR (Pendidikan dan Pengajaran), 2017)
This research is motivated by the low ability of students in writing text announcement in class VII SMP Negeri 7Rambah Rokan Hulu. This study aims to improve the skills of writing text announcement of students of class VIIof SMP Negeri 7 Rambah Rokan Hulu, which is held for 1 month. The subjects of this study are the students ofclass VII of SMP Negeri 7 Rambah Rokan Hulu with 31 people, consisting of 14 male students and 17 femalestudents. The form of research is classroom action research. This research instrument consists of written testand data collection instrument in the form of observation sheet of teacher activity and student activity. Based onthe results of analysis and discussion can be concluded that the implementation of guided writing activitystrategy (SAMT) can improve the skills of writing text announcements to students of class VII SMP Negeri 7Rambah Rokan Hulu. This success can be seen from the students' writing skill in the initial data only get thepercentage of 64.0% with the medium category, in cycle I get the percentage of 75.0% with the mediumcategory. In the second cycle has increased percentage of 84.8% with high category.